2020
DOI: 10.3390/ijms21134762
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Stiffness and Composition Regulate the Myofibroblast Differentiation of Vaginal Fibroblasts

Abstract: Fibroblast to myofibroblast differentiation is a key feature of wound-healing in soft tissues, including the vagina. Vaginal fibroblasts maintain the integrity of the vaginal wall tissues, essential to keep pelvic organs in place and avoid pelvic organ prolapse (POP). The micro-environment of vaginal tissues in POP patients is stiffer and has different extracellular matrix (ECM) composition than healthy vaginal tissues. In this study, we employed a series of matrices with known stiffnesses, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
7
34
0
Order By: Relevance
“…Higher proliferation, contractility and activation of fibroblasts are all reported as responses to a stiffer environment (42-44). In this regard, the proliferation and high viability of fibroblasts grown on both soft and stiff hydrogels observed in this study were comparable to observations from previous investigations (43, 45, 46). Furthermore, the morphology of fibroblasts on soft gels was comparable to fibroblasts on stiff gels.…”
Section: Discussionsupporting
confidence: 92%
“…Higher proliferation, contractility and activation of fibroblasts are all reported as responses to a stiffer environment (42-44). In this regard, the proliferation and high viability of fibroblasts grown on both soft and stiff hydrogels observed in this study were comparable to observations from previous investigations (43, 45, 46). Furthermore, the morphology of fibroblasts on soft gels was comparable to fibroblasts on stiff gels.…”
Section: Discussionsupporting
confidence: 92%
“…Differentiation of fibroblasts to myofibroblasts as evidenced by the increase in α-SMA and collagen gene expression was more pronounced in cells seeded on POP-ECMs which were stiffer than ECMs derived from healthy tissues. It was concluded that when vaginal fibroblasts are seeded on prolapsed ECM, they differentiate into myofibroblast as they recognize surfaces as granulation tissues that need to be remodeled [ 77 ]. Prolonged exposure of vaginal fibroblasts to an abnormal prolapsed matrix results in phenotypical changes.…”
Section: Role Of Fibroblasts In Wound Healing and Tissue Regenerationmentioning
confidence: 99%
“…The expression of α-SMA depends on the concentration of TGF-β1, and is usually abundant in fibroblasts near a scar to assist in scar contraction ( Huang et al, 2001 ; Shinde et al, 2017 ). The contractile protein α-SMA induces transdifferentiation of fibroblasts into myofibroblast, which excrete ECM compounds such as collagen I and III, as well as play a key role in wound closure and ECM contraction ( Ruiz-Zapata et al, 2020 ). Myofibroblasts, also known as contractile cell, increase ECM rigidity by enhancing integrin binding, and cause tissue fibrosis in severe cases ( Klingberg et al, 2013 ).…”
Section: Cancer Mechanomodulationmentioning
confidence: 99%